Sosialisasi Perpanjangan Surat Izin Mengemudi (Sim) C Secara Online pada Aplikasi Digital Korlantas sebagai Pelayanan Publik - Kusumaningsih, Rila; Dwi Yulianingsih (Insan Kreasi Media, 2023)
Every person who drives a motor vehicle on the road is required to have a Driver's License (SIM) in accordance with the type of motor vehicle being driven. Regulation of the Indonesian National Police Number 5 of 2021 concerning the Issuance and Marking of Driver's License (SIM), there are provisions for the issuance of renewal of Driver's License (SIM). The Indonesian National Police has developed technology by creating the korlantas digital application. The korlantas digital application in its presence has many advantages that can be used by its users and can be ensured to maintain the personal data of its users. This korlantas digital application has a Digital ID, or is a technological development to be able to represent digital from a physical identity that is stored online with an encrypted data security system. In addition, this korlantas digital application also develops biometric authentication or face recognition with a liveness feature that can be directly connected to the user's E-KTP biometric data and ensures user data is protected by the system. The reality in the field is that there are still many people who extend their SIM offline or come directly to SATPAS, so this service is carried out so that online SIM renewal can be done by all levels of society because it is proven to be effective and efficient. The method used in the implementation of this legal service is by conducting socialization or legal counselling regarding the importance of orderly driving by having a SIM and extending the sim c online. The purpose of this legal counselling service is to create awareness about the importance of traffic safety, the importance of having legal awareness and introducing Korlantas digital applications to students by involving the younger generation, safety messages can be spread more effectively.